ANALISIS POTENSI PAJAK AIR TANAH DAN KONTRIBUSINYA TERHADAP PENERIMAAN PAJAK DAERAH KOTA MEDAN ( STUDI PADA BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH) - Farida Khairani Lubis; Diana Oktavia Lusiana (Universitas Islam Islam Sumatera Utara, 2020)
This study aims to analyze the potential of groundwater tax and its contribution to the regional tax revenue of the city of Medan, with the 2015-2018 observation period. This study uses secondary data. Data analysis techniques used are descritive analysis through 3 stages of calculation obtained from calculate and analyze the Potential, Effectiveness, Contribution and growth rate of groundwater tax. The results of this study are that extracting the potential of groundwater tax in the city of Medan produces a pretty good percentage from 2915-2018 extracting potential groundwater taxes by an average of 90%. The effectiveness of groundwater taxes from 2015-2018 always produces effective results, namely always getting 90% upward. The contribution given by the groundwater tax to local tax revenues has not been significant and has not been well realized it is proven that from year to year it always goes up and in 2018 the contribution of groundwater tax decreases. The biggest contribution of groundwater tax is 1,08% in 2015. The growth rate of municipal groundwater tax in the field produces fluctuating results and the dominant up and down can be seen from the result of the calculated data.